Processing Biochar from Solid Waste of Arenga Pinnata Flour Industry - Susanti Rina, ST, MT (Eksergi)
Arenga pinnata solid waste can be used as biochar-making material because it contains biomass agriculture and forestry residue. This research purposed to know the effect of pyrolysis in yield and characteristic of biochar as soil amendment. The research done by making model and practice the model. The variables of this research were : temperature, biochar yield, C-organic content, water content, pH, N, P, and K. The raw materials weight that used in each pyrolysis process is 200 grams.The result from this research are the highest biochar yield from arenga pinnata with 200 grams of raw materials weight was at 300 – 500 °C of temperature and 210-240 minutes of processing time with >30% of yield. The test with temperature variations show : 1) at 300-400°C of temperature acquired 4,45% of water content, 5,6 of pH, 14,63% of C-organic content, 0,71% of Nitrogen, 0,10% of Phosphor, and 0,63% of Kalium, 2) at 400-500°C of temperature acquired 5,62% of water content, 5,26 of pH, 13,49% of C-organic content, 0,73% of Nitrogen, 0,13% of Phosphor, and 0,49% of Kalium, 3) at 500-600°C of temperatur acquired 3,22% of water content, 6,1 of pH, 15,66% of C-organic content, 0,92% of Nitrogen, 0,09% of Phospor, and 0,58% of Kalium. The results from this research were able to fulfill the regulation as soil amendment determined by International Biochar Initiative (2010).